SUPER ENERGY SAVING LOCKING SYSTEM (SES- LOCK) - Sivarao, Subramonian; Aziz, Alif; Hambali, A; Salleh, Mohd Rizal; T.J.S, Anand; Raja, Izamshah; Nur, izan; A.R.M, Warikh (2013)
There are various types of automatic door locking system available worldwide. Through the increasing number of doors inevitably, the selection of automatic door locking system becomes a vital issue. The consumer should be conscious on the effectiveness and design characteristics provided by the particular door lock systems as refer to their desire. The most recent and widely used Electromagnetic (EM) lock in the market holds many drawbacks and disadvantages such are very costly where they continuously consume electricity (almost 24 hours) to hold the door in locking position, requires a backup battery in case of power failure, can be electrically and mechanically hacked easily. Therefore, Super Energy Saving Locking System (SES-Lock) was designed inversely, in such a way that does not required power supply to lock or to hold the door in locking position. Hence, power consumption can be saved up to 90% as compared to EM- Lock type. Back-up battery is not necessarily required during a power failure, where the system can still be locked as usual and can be easily opened using incorporated manual administrative key (fail safe and fail secure). This locking system can easily be operated by using 6 - 12V DC and very much difficult to be hacked or vandalized in electrically or mechanically as it is strongly held by mechanical element. The futuristic SES-Lock is expected to replace the huge numbers of EM Lock for security application globally as it saves a lot of energy while providing enhanced security of an access system.